2012
DOI: 10.3389/fphys.2012.00218
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Nitric Oxide Synthases in Aging: Therapeutic Opportunities

Abstract: Vascular aging is the term that describes the structural and functional disturbances of the vasculature with advancing aging. The molecular mechanisms of aging-associated endothelial dysfunction are complex, but reduced nitric oxide (NO) bioavailability and altered vascular expression and activity of NO synthase (NOS) enzymes have been implicated as major players. Impaired vascular relaxation in aging has been attributed to reduced endothelial NOS (eNOS)-derived NO, while increased inducible NOS (iNOS) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 143 publications
2
88
0
8
Order By: Relevance
“…However, the polymorphisms of rs2070744 (T>C) and rs3918181 (A>G) in the eNOS gene lacked any association with EH in this ethnic group. eNOS is considered the main source of NO in the vascular endothelium (Cau et al, 2012), in which eNOS diffuses into vascular smooth muscle cells and activates guanylate cyclase, leading to vasodilatation (Jachymova et al, 2001). An increasing number of genetic studies have demonstrated that DNA polymorphisms in the eNOS gene are associated with coronary artery disease, such as hypertension (Senthil et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, the polymorphisms of rs2070744 (T>C) and rs3918181 (A>G) in the eNOS gene lacked any association with EH in this ethnic group. eNOS is considered the main source of NO in the vascular endothelium (Cau et al, 2012), in which eNOS diffuses into vascular smooth muscle cells and activates guanylate cyclase, leading to vasodilatation (Jachymova et al, 2001). An increasing number of genetic studies have demonstrated that DNA polymorphisms in the eNOS gene are associated with coronary artery disease, such as hypertension (Senthil et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related vascular pathologies such as endothelial dysfunction, vascular inflammation, calcification, and stiffness are the most important reasons for increased cardiovascular morbidity and mortality, and one of the leading causes of their underlying mechanism would be oxidative stress (Cau et al 2012;Ungvari et al 2010;Demirci et al 2005). Vascular inflammation can be the source of enhanced reactive oxygen species (ROS) and this oxidative stress may result in development and progression of such cardiovascular diseases as atherosclerosis and hypertension (Wu et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular inflammation can be the source of enhanced reactive oxygen species (ROS) and this oxidative stress may result in development and progression of such cardiovascular diseases as atherosclerosis and hypertension (Wu et al 2002). Increased ROS in aging inactivates nitric oxide (NO) which is released by endothelium for maintenance of vascular homoeostasis (Cau et al 2012;Taubert et al 2004;Ungvari et al 2010). Additionally, in this term, cardiovascular risk increases due to the lost benefit of estrogens (Miller et al 2007;Stice et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO), the main vasodilator, is derived by endothelial nitric oxide synthase (eNOS) from healthy endothelium or the inducible form of NOS (iNOS) in inflammatory conditions. When NO reacts with ROS in oxidative stress, this situation results in a decrease in NO bioavailability and production of harmful substances such as peroxinitrite in aged vasculature (Cau et al, 2012;Demirci et al, 2005). On the other hand, the activity of cyclooxygenase (COX) also regulates vascular contraction and/or relaxation by generating prostaglandins.…”
Section: Introductionmentioning
confidence: 99%
“…The inducible form of COX in inflammation is known as COX-2. Hence, pharmacologic modulation of these vasoactive mediators and enzymes may represent therapeutic benefit to prevent the progression of cardiovascular aging (Cau et al, 2012;Wong et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%